MERANCANG MEDIA PEMBELAJARAN INTERAKTIF ARTYCULATE STORYLINE BAGI GURU-GURU DI SEKOLAH BINAAN SIKL MALAYSIA - Dwijayanti, Renny; Marlena, Novi; Patrikha, Finisica Dwijayati; Irawati, Winaika (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The development of.learning media using Articulate Storyline is becoming increasingly important in the context of modern student-centered education. When problems arise regarding the lack of teacher creativity and teacher skills in utilizing learning media, it causess students too easily get bored in the learning process. This activity is divided into 3 parts, namely: (1) Initial coordination stage of activities, (2) Implementation of activities, and (3) Evaluation of activities. In general, the ability of participants to understand learning media using the articulate storyline application is good with a classical completion value indicator (KKM) of 70. Based on the pre-test value of training participants who have a completion value of 67.5% and a post-test value of 81.7%. From the results of the training on making learning media, it can be identified that participants are very enthusiastic in participating in the training from the high level of attendance of training participants and the results of making good learning media after training.